Legal Certainty For The Judiciary That Is Authorized To Adjudicate Corruption Cases That Occurred In Basarnas RI - Putra, Reza Alamsyah; Arafat, Zarisnov; Abas, Muhamad (Dinasti Research, 2025)
Article 42 of the Corruption Eradication Commission Law grants the KPK (Corruption Eradication Commission) coordinating authority to oversee the investigation, inquiry, and prosecution of corruption crimes jointly committed by legal subjects under the jurisdiction of both military and general courts. The normative juridical research method, as a legal research approach, bases its analysis on literature review or secondary data sources as the primary foundation of the study, conducted through an in-depth examination of legal regulations and various literature references relevant to the issue under review. Based on an analysis of the relevant statutory provisions, it can be concluded that the Basarnas corruption case involving military personnel should be adjudicated by the Corruption Court, with several legal considerations. The Corruption Court is the competent body to try corruption cases within the National Search and Rescue Agency of the Republic of Indonesia, while maintaining institutional coordination between the KPK and the Indonesian National Armed Forces (TNI) as mandated by the Constitutional Court's decision. An in-depth analysis of the applicable statutory provisions indicates that the legal provisions regarding jurisdiction over corruption cases involving military personnel have undergone a paradigmatic shift from a personal jurisdiction approach to a subject matter jurisdiction approach. Based on this ruling, and considering that the Basarnas corruption case was initially investigated and discovered by the KPK, the Corruption Court is the competent body to adjudicate the case, including that of Air Marshal Henri Alfiandi as an active member of the TNI.